Attitude of general dental practitioners to pediatric patients and preventive dentistry - Ahmet Aras; Mehmet Sinan Dogan (Wolters Kluwer Medknow Publications, 2019)
Background: Dental education shapes the attitudes and professional behavior of dentists when treating pediatric patients. We evaluated the extent to which general dental practitioners (GDPs) in private and public hospitals were willing to treat pediatric patients as well as their attitude to preventive dentistry. Materials and Methods: A web-based questionnaire comprising 18 questions was E-mailed to 600 GDPs across Turkey. Descriptive statistics and the Pearson Chi-squared test were used for statistical analysis. Results: The response rate was 63.6% (n = 382). Of the 382 GDPs, 40 were unwilling to treat pediatric patients, whereas 74 stated that they treated such patients rarely. The GDPs were most unwilling to treat pediatric patients under 4 years of age (35.1%). The most frequent reason cited for unwillingness to treat was the uncooperative behavior of pediatric patients (77.2%). Of the GDPs, 51.6% and 56.8% preferred topical fluoride and fissure sealant, respectively, as preventive measures. Conclusions: GDPs are unwilling to treat pediatric patients due to their lack of cooperation. To overcome this, theoretical and practical training in pediatric dentistry behavior management techniques should be promoted.